Olfactory Functions in Adults With Autism Spectrum Disorders. (March 2017) - Addo, Rebecka N.; Wiens, Stefan; Nord, Marie; Larsson, Maria
Autism spectrum disorders (ASD) are often characterized by atypical sensory behavior (hyper- or hyporeactivity) although evidence is scarce regarding olfactory abilities in ASD; 16 adults with high-functioning ASD (mean age: 38.2, SD : 9.7) and 14 healthy control subjects (mean age: 42.0 years, SD : 12.5) were assessed in odor threshold, free and cued odor identification, and perceived pleasantness, intensity, and edibility of everyday odors. Although results showed no differences between groups, the Bayes Factors (close to 1) suggested that the evidence for no group differences on the threshold and identification tests was inconclusive. In contrast, there was some evidence for no group differences on perceived edibility (BF01 = 2.69) and perceived intensity (BF01 = 2.80). These results do not provide conclusive evidence for or against differences between ASD and healthy controls on olfactory abilities. However, they suggest that there are no apparent group differences in subjective ratings of odors.